Less Severe but Prolonged Course of Acute Hepatitis A in Human Immunodeficiency Virus (HIV)–Infected Patients Compared With HIV-Uninfected Patients During an Outbreak: A Multicenter Observational Study. (17th April 2018) - Lee, Yu-Lin; Chen, Guan-Jhou; Chen, Nan-Yu; Liou, Bo-Huang; Wang, Ning-Chi; Lee, Yuan-Ti; Yang, Chia-Jui; Huang, Yu-Shan; Tang, Hung-Jen; Huang, Shie-Shian; Lin, Yi-Chun; Cheng, Chien-Yu; et al.
Abstract : During an AHA outbreak, we found that HIV-infected patients had a lower severity, but delayed resolution, of AHA than HIV-uninfected patients. Better viral suppression by cART alleviated the impact of HIV infection on the disease course of AHA in HIV-infected patients. Abstract: Background: This multicenter retrospective cohort study aimed to compare the clinical presentations and evolution of acute hepatitis A (AHA) between human immunodeficiency virus (HIV)–infected patients and HIV-uninfected counterparts during the AHA outbreak. Methods: Clinical and laboratory data were collected from the medical records of the patients with AHA at the 14 hospitals around Taiwan between May 2015 and May 2017. Results: A total of 297 adult patients with AHA were included during the study period. Their mean age was 31.4 years (range, 19.0–76.1 years); 93.4% were men and 58.6% were men who have sex with men. Of 265 patients with known HIV serostatus, 166 (62.6%) were HIV infected. Compared with HIV-uninfected patients, HIV-infected patients had a lower peak alanine aminotransferase (ALT) level (median, 1312 vs 2014 IU/L, P = .003), less coagulopathy (6.0% vs 16.2%, P = .007), and less hepatomegaly or splenomegaly on imaging studies, but a higher rate of delayed resolution of hepatitis (38.8% vs 21.3%, P = .009). HIV-infected patients with plasma RNA load <1000 copies/mL while receiving combination antiretroviral therapy (cART) had a higher peak ALT level (median, 1420 vs 978 IU/L, P = .006) and less delay in resolution of hepatitis (30.6% vs 48.8%, P = .047) than patients without cART or with plasma RNA load ≥1000 copies/mL. Conclusions: During an AHA outbreak, HIV-infected patients had a lower severity, but delayed resolution, of AHA than HIV-uninfected patients. Better viral suppression by cART alleviated the impact of HIV infection on the disease course of AHA in HIV-infected patients.